Characteristics of a resonant iris microwave-induced nitrogen plasma - Goncalves, Daniel A. [UNESP]; McSweeney, Tina; Donati, George L. (Royal Society of Chemistry (RSC), 2016)
In this work, we use the Boltzmann plot, Saha's equation and the Mg II/Mg I signal ratio to determine temperature (T), electron number density (ne) and robustness of different regions of a microwave-induced nitrogen plasma. A 2-D profile based on plasma observation position and nebulization flow rate is generated for each of these properties and their effects on sensitivity, accuracy and matrix-related interferences in microwave-induced plasma optical emission spectrometry (MIP OES) are evaluated. Plasma temperatures vary between 4220 and 5360 K by changing nebulization flow rate and plasma observation position. These same instrumental parameters are varied to produce ne values in the 0.47-3.72 × 1013 cm-3 range, and Mg II/Mg I ratios between 0.26 and 2.01. Limits of detection (LODs) were calculated for different T and ne conditions, and for analytes with a wide range of Esum values (Esum = ionization energy + excitation energy). The best LODs were calculated for determinations at high ne plasma regions. More robust plasma conditions allowed for more accurate results when determining analytes with Esum > 9 eV or < 3 eV. For intermediate Esum elements, the best recoveries in complex sample analyses were obtained at high ne conditions. Although the microwave applied power is fixed at 1000 W for the commercial MIP OES evaluated, one can still control plasma conditions by varying other operating parameters, which may contribute to fewer matrix effects, better accuracies and lower LODs.